HUBUNGAN PENGETAHUAN KELUARGA DENGAN LAMA WAKTU KEDATANGAN PASIEN STROKE ISKEMIK KE IGD RSUD JOMBANG - Kusyani, Asri (LPPM STIKes Bahrul Ulum Jombang, 2019)
Patients who experience stroke signs and symptoms often experience delays in coming to the hospital, strokes have a time limit to get help immediately, the delay in bringing stroke patients to the hospital results in disability and paralysis. Delays that occur are often associated with knowledge of the signs and symptoms of stroke and the pattern of seeking health assistance determined by the family. The purpose of this study was to determine the relationship of family knowledge with the length of time the arrival of ischemic stroke patients to the emergency department of Jombang Hospital. The research design used was analytical with a cross-sectional approach. The sampling technique used was purposive sampling in the families of stroke patients with a total of 60 respondents. Research location in Jombang Regional General Hospital. Analyze data using Spearman rank. Bivariate results with the Spearman Rank test of knowledge with the length of time the stroke patients arrived (p = 0,000), the knowledge gained OR = 43,083. Health Officers provide counseling to patients and stroke families to be able to provide information on signs and symptoms of stroke and the importance of immediately bringing patients to the hospital to get appropriate and fast health services. This study concludes that there is a significant relationship between knowledge with the length of time the stroke patient arrives to come to the emergency room.